2020
DOI: 10.1103/physrevresearch.2.023066
|View full text |Cite
|
Sign up to set email alerts
|

QCD Kondo excitons

Abstract: The QCD Kondo effect is a quantum phenomenon when the heavy quarks (c, b) exist as impurity particles in quark matter composed of the light quarks (u, d, s) at extremely high density. This is analogous to the famous Kondo effect in condensed matter physics. In the present study, we show theoretically the existence of the "QCD Kondo excitons", i.e., the bound states of light quarks and heavy quarks, as the lowest-excitation modes above the ground state of the quark matter governed by the QCD Kondo effect. Those… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Such "relativistic" Kondo effects can occur in relativistic-fermion systems including impurities, such as graphene (see Ref. [6] for a review), Dirac/Weyl semimetals [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], dense nuclear matter [24][25][26][27], and dense quark matter [13,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Among them, the QCD Kondo effect [24,28] is induced by the color exchange interaction between a light quark and an impurity quark, which is based on quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%

Kondo effect with Wilson fermions

Ishikawa,
Nakayama,
Suzuki
2021
Preprint
Self Cite
“…Such "relativistic" Kondo effects can occur in relativistic-fermion systems including impurities, such as graphene (see Ref. [6] for a review), Dirac/Weyl semimetals [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], dense nuclear matter [24][25][26][27], and dense quark matter [13,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Among them, the QCD Kondo effect [24,28] is induced by the color exchange interaction between a light quark and an impurity quark, which is based on quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%

Kondo effect with Wilson fermions

Ishikawa,
Nakayama,
Suzuki
2021
Preprint
Self Cite
“…In fact, it was shown that the Kondo effect arises in nuclear matter when Σ c and Σ * c baryons or D and D * mesons exist as impurities, where the spin and/or isospin exchange serves as the non-Abelian interaction [3,[5][6][7]. In addition, many works on Kondo effect in a relativistic system have been done in the literatures [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In this way, the interdisciplinary study bridging condensedmatter physics and QCD/hadron physics focused on the Kondo effect is attracting attention.…”
Section: Introductionmentioning
confidence: 99%
“…2 While the Kondo effect was originally found in metal including impurities in the context of condensed-matter physics [13][14][15][16][17], it has been theoretically shown to emerge in quark matter [18,19] (See Refs. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] for related discussions). 3 The Kondo effect is known to change the transport phenomena characteristically.…”
Section: Introductionmentioning
confidence: 99%